Harmoniser politiques sociale et environnementale : évaluation de l’impact d’une réhabilitation de quartiers défavorisés sur les émissions de CO2 liées aux déplacements - Louafi Bouzouina; Jean-Pierre Nicolas (VertigO)
This paper is about the environmental impact, measured by the CO2 emissions of rehabilitation of two segregated neighborhoods in the northern suburbs of Lyon (Vaulx-en-Velin). Its objective is to test the impact of the residential relocations related to a social mix policy on the CO2 emissions of the daily mobility of the inhabitants at different scales. The CO2 emissions increases with the income of households and the distance to the center (linked to the growth of the vehicle ownership and the distances covered daily) on the scale of the agglomeration. On a local scale, the search for a better social mix leads to an increase in the CO2 emissions: it would pass from 0.515 tons to 0.74 t/year/cap. Lastly, according to the orientation of the residential migrations, the CO2 emissions of the concerned populations can drop (case of a centring of the populations, with a passage from 0.81 to 0.648 t/year/cap as it can raise (case of a urban sprawl, with an increase of 0.515 to 0.822 tons).